Monkeypox-related knowledge and vaccination willingness among HIV-diagnosed and -suspected males: a cross-sectional survey in Changsha - Yingying Zhou; Jiemin Wang; Zhi Xie (Frontiers in Public Health)
ObjectiveThis study aimed to update baseline data on monkeypox (mpox)-related knowledge and vaccination willingness among human immunodeficiency virus (HIV) diagnosed and suspected males.MethodsThe cross-sectional survey was conducted in Changsha, a provincial capital in China, during 5 JULY to 5 SEPTEMBER 2023. Among the three study groups, the participants in the “previously diagnosed” group were recruited from a cohort of HIV-infected patients. The “newly diagnosed” and the “suspected” groups were recruited from the outpatients and grouped according to their confirmatory test results. The the exploratory factor analysis was firstly applied to capture the latent structure of participants’ response to the questionnaire about monkeypox. The component and factor scores were compared between groups using the Kruskal-Wallis H tests. The chi-square test was then used to assess the difference of mpox vaccination willingness between MSM and non-MSM in each group. Finally, multivariate logistic regression analysis was performed to identify the determinants of vaccination willingness.ResultsA total of 481 males were included in the final analysis. The results revealed that there was a gap in knowledge about monkeypox between the three participant groups. The vaccination willingness rate of HIV-infected participants was above 90%, while the rate in the HIV-suspected group was 72.60%. Multivariate logistic regression analysis revealed that the previously diagnosed group (adjusted odds ratio [aOR] = 0.314, 95% confidence interval [CI]: 0.105–0.940) and the suspected group (aOR = 0.111, 95% CI: 0.034–0.363) had a lower level of vaccination willingness and they were referred to the newly diagnosed group. Participants in the age groups ranging 25–34 (aOR = 0.287, 95% CI: 0.086–0.959) and 35–44 (aOR = 0.136, 95% CI: 0.039–0.478) years showed a lower level of vaccination willingness, referred to the 15–24 year age group. A better knowledge about monkeypox was associated with a higher level of vaccination willingness (aOR = 1.701, 95% CI: 1.165–2.483). Additionally, a considerable percentage of heterosexual individuals in each group indicated their acceptance of monkeypox vaccines.ConclusionAn overall high level of vaccination willingness was observed among HIV-infected and-suspected male individuals with disparities noted among those with different HIV infection status, knowledge levels of monkeypox, and age. Addressing the existing knowledge gap and engaging people with persistent risks—regardless of their sexual orientation—for a timely HIV diagnosis may facilitate vaccine-based mitigation measures against monkeypox.